General Richard Montgomery and the American Revolution : From Redcoat to Rebel. - Shelton, Hal T. (American Social Experience S., 1994)
Brave, humane, and generous ... still he was only a brave, humane, and generous rebel; curse on his virtues, they've undone this country. --Member of British Parliament Lord North, upon hearing of General Richard Montgomery's death in battle against the British. At 3 a.m. on December 31, 1775, a band of desperate men stumbled through a raging Canadian blizzard toward Quebec. The doggedness of this ragtag militia--consisting largely of men whose short-term enlistments were to expire within the next 24 hours--was due to the exhortations of their leader. Arriving at Quebec before dawn, the troo.